Ketidaknyamanan Pegawai Pada Proses Integrasi Post Merger : Studi Kasus Pada Integrasi Terminal Pelindo Kepada Pelindo TPK - Emil Puji Arifan (Cakrawala Repositori IMWI, 2023)
One of the government's strategic programs to reduce national logistics costs by realizing a consolidation strategy for the unification of BUMN port services in 2021. A total of 15 container terminals that were originally managed from each Pelindo, will switch management (acquired) by Pelindo TPK. These changes may cause inconvenience. This then causes the phenomenon of change related to inconvenience which is interesting to study. This research was conducted using a qualitative method in the form of a case study. The population of this research is container terminal employees. The data collection method used was by conducting interviews and observations. The data analysis conducted in this study used critical incident technique (CIT) analysis. Employee discomfort is caused by employee concerns over the integration that occurs. The reaction/response shown by employees is shocked by the phase of change for the integration that occurs. The impact/consequence of the inconvenience is that it has the potential to cause disappointment from employees, thus causing problems related to the changes that occur, and will lead to rejection behavior from employees.